Strategi Penggalian Sumber Dana dan Partisipasi Multipihak dalam Pembiyayaan Pendidikan Islam: Studi Kasus di SMA Muhammadiyah 5 Yogyakarta (Jurnal Manajemen Bisnis Digital Terkini, 2026)
This study explores strategies for mobilizing financial resources and multi-stakeholder participation in Islamic education financing to achieve institutional financial independence. The research was conducted at SMA Muhammadiyah 5 Yogyakarta, a private Islamic secondary school implementing a financing model based on Sharia values and Total Quality Management (TQM) principles. A qualitative case study approach was employed, utilizing primary data from in-depth interviews with school administrators and observations of financial management practices, as well as secondary data from budget plans, government funding reports, and cooperation documents with philanthropic institutions. Data were analyzed using an interactive model involving data reduction, data presentation, and inductive conclusion drawing. The findings reveal that financial independence is strengthened through diversified funding sources, including government support, parental contributions, Islamic philanthropy, and school-based business units. Transparency and accountability are maintained through open financial reporting and stakeholder involvement. The study highlights that integrated Islamic education financing aligned with Sharia values and TQM enhances institutional sustainability, educational quality, and organizational competitiveness.